Brazilian Black Women are at Higher Risk for COVID-19 Complications: An Analysis of REBRACO, a National Cohort - Dantas-Silva, Amanda; Surita, Fernanda Garanhani; Souza, Renato; Rocha, Leila; Guida, José Paulo; Pacagnella, Rodolfo; Tedesco, Ricardo; Fernandes, Karayna; Martins-Costa, Sérgio; Peret, Frederico; Feitosa, Francisco; Traina, Evelyn; Cunha Filho, Edson; Vettorazzi, Janete; Haddad, Samira; Andreucci, Carla; Correa Junior, Mario; Dias, Marcos; Oliveira, Leandro de; Melo Junior, Elias; Luz, Marília; Cecatti, Jose Guilherme; Costa, Maria Laura (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To evaluate the impact of the race (Black versus non-Black) on maternal and perinatal outcomes of pregnant women with COVID-19 in Brazil.Methods This is a subanalysis of REBRACO, a Brazilian multicenter cohort study designed to evaluate the impact of COVID-19 on pregnant women. From February 2020 until February 2021, 15 maternity hospitals in Brazil collected data on women with respiratory symptoms. We selected all women with a positive test for COVID-19; then, we divided them into two groups: Black and non-Black women. Finally, we compared, between groups, sociodemographic, maternal, and perinatal outcomes. We obtained the frequency of events in each group and compared them using X2 test; p-values < 0.05 were considered significant. We also estimated the odds ratio (OR) and confidence intervals (CI).Results 729 symptomatic women were included in the study; of those, 285 were positive for COVID-19, 120 (42.1%) were Black, and 165 (57.9%) were non-Black. Black women had worse education (p = 0.037). The timing of access to the health system was similar between both groups, with 26.3% being included with seven or more days of symptoms. Severe acute respiratory syndrome (OR 2.22 CI 1.17–4.21), intensive care unit admission (OR 2.00 CI 1.07–3.74), and desaturation at admission (OR 3.72 CI 1.41–9.84) were more likely to occur among Black women. Maternal death was higher among Black women (7.8% vs. 2.6%, p = 0.048). Perinatal outcomes were similar between both groups.Conclusion Brazilian Black women were more likely to die due to the consequences of COVID-19.
Keywords: COVID-19; Obstetrics; Racial disparities; Black women